TRANSFORMASI KETELADANAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MEMBENTUK RELIGIUSITAS SISWA DI MADRASAH TSANAWIYAH BUSTANUL ULUM KARANGSUKO - Siti Fatimatur Rohmah; Nur Qomari (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study explores the role of exemplary behavior of Islamic Religious Education (PAI) teachers at MTs Bustanul Ulum in shaping students' religiosity. The findings show that teachers' exemplary behavior applies Islamic values in daily life, creating a supportive religious environment for internalizing these values. Despite challenges like social media influence and time constraints, institutional support and digital technology can enhance role modeling effectiveness. The study concludes that exemplary behavior of PAI teachers is a key strategy in sustainable character education, developing academically excellent and morally mature students.